2001
DOI: 10.1097/00001721-200101000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected hyperhomocysteinemia in chronically anticoagulated patients

Abstract: Hyperhomocysteinemia is a risk factor for arterial and venous thrombosis. The aim of this study was to evaluate plasmatic homocysteine levels in patients under chronic anticoagulant treatment with dietary restriction of green vegetables. This kind of food is a very important source not only of vitamin K but also of folates, which are involved in Hcy metabolism. It is known that the lower the folate levels, the higher the Hcy concentration, so we suspected that these patients could show hyperhomocysteinemia. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…All patients were consuming a regular diet and none reported the use of B 1 , B 12 , or folic acid, which may have influenced tHcy concentrations. The effect of diet (through the consumption of green vegetables containing folate and vitamin K) has been previously addressed 11 ; a low folate diet may have had an effect on tHcy concentrations in our patient cohort. However, in our anticoagulation clinic, we do not recommend a "poor vegetable" diet.…”
Section: Discussionmentioning
confidence: 93%
“…All patients were consuming a regular diet and none reported the use of B 1 , B 12 , or folic acid, which may have influenced tHcy concentrations. The effect of diet (through the consumption of green vegetables containing folate and vitamin K) has been previously addressed 11 ; a low folate diet may have had an effect on tHcy concentrations in our patient cohort. However, in our anticoagulation clinic, we do not recommend a "poor vegetable" diet.…”
Section: Discussionmentioning
confidence: 93%
“…The first study, confined to males in the Physicians' Health Study, investigated the risk of a first venous thromboembolic event over a 12-year period. 39 A homocysteine level greater than the 95th percentile of the distribution of the control group was associated with a relative risk of a first-time venous thrombosis of 1.6 (95% CI 0.8-3.3). The relative risk was greater for idiopathic venous thrombosis (3.4; 95% CI 1.6-7.3).…”
Section: Prospective Studiesmentioning
confidence: 91%
“…The difference in homocysteine levels between those with TT versus CC genotypes is greater among those with low folate or riboflavin status than in those with normal or high levels of these vitamins 26 Individual studies and a previous metaanalysis included too few cases to produce reliable evidence for or against an association of this polymorphism with venous thrombosis. Some studies have reported an interaction between hyperhomocysteinemia or MTHFR C677T and Factor V Leiden 39 or the G20210A polymorphism and venous thrombosis. 49…”
Section: Genetic Studiesmentioning
confidence: 99%
“…Some evidence, mainly anecdotal, suggests that patients sometimes misinterpret this advice and reduce intake of dark-green leafy vegetables rather than trying to maintain a steady intake [7]. As this food category is an important dietary source of folate, there is a risk that the folate status of patients taking oral anticoagulants may be compromised.…”
Section: Introductionmentioning
confidence: 99%